2018
DOI: 10.15809/irriga.2016v21n2p409-424
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho De Um Modelo Hidrológico Concentrado E De Um Semidistribuído Na Predição De Vazões Diárias

Abstract: DESEMPENHO DE UM MODELO HIDROLÓGICO CONCENTRADO E DE UM SEMIDISTRIBUÍDO NA PREDIÇÃO DE VAZÕES DIÁRIAS  DONIZETE DOS REIS PEREIRA1; EDUARDO MORGAN ULIANA2; MAURO APARECIDO MARTINEZ3 E DEMETRIUS DAVID DA SILVA4  1Prof. do Instituto de Ciências Agrárias,  UFV/Campus de Florestal. Rod. LMG 818, km 6. CEP 35690-000 Florestal (MG), Brasil. e-mail: doniagri@yahoo.com.br2Prof. do Instituto de Ciências Agrárias e Ambientais, ICAA/UFMT. Avenida Alexandre Ferronato – 1200, Setor Industrial. CEP 78557-267 Sinop (MT), Bras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
3
3
7
Order By: Relevance
“…However, the 60-40% arrangement was the one which presented less deviation in the validation phase, with 12.6% when compared to the average of the observed data. The deviations found were minor in the study of Pereira et al (2016b) in which the deviation represented 18% of the average observed in the calibration and 20.6% in the validation.…”
Section: -50%mentioning
confidence: 72%
See 1 more Smart Citation
“…However, the 60-40% arrangement was the one which presented less deviation in the validation phase, with 12.6% when compared to the average of the observed data. The deviations found were minor in the study of Pereira et al (2016b) in which the deviation represented 18% of the average observed in the calibration and 20.6% in the validation.…”
Section: -50%mentioning
confidence: 72%
“…It is possible to observe agreement between the data observed and simulated by IPH II, but in all settings the model had difficulty in representing the peak values, mainly in the validation. According to Pereira et al (2016b) peak values are naturally difficult to simulate by hydrological models due to rainfall variability and low concentration time in river basins. This difficulty is also found by Andrade (2013) and Pereira et al (2014aPereira et al ( , 2014b.…”
Section: -50%mentioning
confidence: 99%
“…The Nash-Sutcliffe index has been applied effectively in the evaluation of the performance of hydrological models (Miranda et al, 2014;Pereira et al, 2016), Global radiation models (Deo et al, 2016), and models of dry matter accumulation and rice yield (Ribas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nota-se que o modelo SARIMA foi eficaz principalmente nos períodos de recessão, com boa aderência às vazões mínimas observadas. De acordo com Pereira et al (2016), a previsão de vazões mínimas subsidia o dimensionamento de sistemas de bombeamento para irrigação, a previsão de estiagens críticas e a determinação de vazões outorgáveis, sendo esta a principal finalidade identificada para o modelo SARIMA ajustado para a BHMAN no presente estudo. Cabe ressaltar que conforme a Figura 10, nota-se dificuldade em prever as vazões máximas, o que pode ser justificado segundo Viola et al (2009) pela maior complexidade da gênese do escoamento superficial direto.…”
Section: Figura 8 -Periodograma Da Série De Vazões Mensaisunclassified